The grand celebration of the innovation and quality month in UiTM 2025 - Ariffin, Nur Syamimi; Aziz, Hamzah (Faculty of Pharmacy, 2025)
Alhamdulillah, praise be to Allah, the Most Gracious and the Most Merciful. The Faculty of Pharmacy, UiTM Puncak Alam, celebrated a historic achievement by successfully organising the grand celebration of UiTM Innovation and Quality Month 2025, in collaboration with the Institute of Quality and Knowledge Management (InQKA) and UiTM Global. The event was held at Dewan Agung Tuanku Chancelor (DATC), UiTM Shah Alam. We were honoured to welcome all UiTM staff to this meaningful event, which also commemorated the 25 anniversary of the Faculty of Pharmacy.